Androgen Receptors Act as a Tumor Suppressor Gene to Suppress Hepatocellular Carcinoma Cells Progression via miR-122-5p/RABL6 Signaling - Tang, Neng; Dou, Xiaolin; You, Xing; Li, Yixiong; Li, Xi; Liu, Guodong (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is a malignant tumor with a high degree of malignancy and a poor prognosis. Androgen receptor (AR) has been reported to play important roles in the regulation of the progression of HCC, but the underlying mechanisms of how AR regulates HCC initiation, progression, metastasis and chemotherapy resistance still need further study. Our study found that AR could act as a tumor suppress gene to suppress HCC cells invasion and migration capacities via miR-122-5p/RABL6 signaling, and the mechanism study further confirmed that miR-122-5p could suppress the expression of RABL6 to influence HCC cells progression by directly target the 3’UTR of the mRNA of RABL6. The preclinical study using an in vivo mouse model with orthotopic xenografts of HCC cells confirmed the in vitro data, and the clinical data gotten from online databases based on TCGA samples also confirmed the linkage of AR/miR-122-5p/RABL6 signaling to the HCC progression. Together, these findings suggest that AR could suppress HCC invasion and migration capacities via miR-122-5p/RABL6 signaling, and target this newly explored signaling may help us find new therapeutic targets for better treatment of HCC.